1989
DOI: 10.1139/f89-079
|View full text |Cite
|
Sign up to set email alerts
|

Origin and Dispersion of Larval Herring (Clupea harengus) in Coastal Waters of Eastern Maine and Southwestern New Brunswick

Abstract: Repetitive surveys of larval herring (Clupea harengus) were undertaken in coastal waters between Mt. Desert, Maine and Saint John, New Brunswick to define the location, timing, and extent of spawning and the distribution of larvae. Three surveys during September and October 1986 showed two separate areas of larval dispersal. The easternmost stations contained low densities of large larvae which were assumed to be part of the annually occurring larval aggregation off Nova Scotia. High densities of small larvae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Townsend et al 1986, Kisrboe et al 1988, Chenoweth et al 1989, and as in the present study, Suthers et al (1989) showed an improved growth ability of cod larvae within the area of retention. The present findings point to the irnportance of a match between distribution of larvae and areadperiods that offers superior conditions for larval life, thus supporting the match/mismatch theory (Hjort 1926, Cushing 1972.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Townsend et al 1986, Kisrboe et al 1988, Chenoweth et al 1989, and as in the present study, Suthers et al (1989) showed an improved growth ability of cod larvae within the area of retention. The present findings point to the irnportance of a match between distribution of larvae and areadperiods that offers superior conditions for larval life, thus supporting the match/mismatch theory (Hjort 1926, Cushing 1972.…”
Section: Discussionsupporting
confidence: 82%
“…The retention of larvae in areas of tidal fronts has been described in a number of studies (e.g. herring: Kierboe et al 1988, Chenoweth et al 1989, Fortier & Gagne 1990cod: Suthers et al 1989), and the profitability of retention areas to larval growth and survival has been much debated. Based on the findings of herring larval distributions, a hypothesis of 'larval retention' was proposed by Iles & Sinclair (1982).…”
Section: Discussionmentioning
confidence: 99%
“…Fronts (transition regions between mixed and stratified water masses) surrounding banks have also been suggested to form distinct zones of separation (between water masses) or aggregation (convergence zones) of larval fish and their prey ( Kingsford, 1990). In tidally energetic areas, tidal fronts ( sensu Pingree et al ., 1974 ) and variations therein are hypothesized to play a significant role in larval dispersal and possibly recruitment processes ( Iles and Sinclair, 1982; Sinclair and Iles, 1985; Heath et al ., 1988 ; Chenoweth et al ., 1989 ; Heath, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Kiarboe e t al. 1988, Chenoweth et al 1989, Fortier & Gagne 1990), a n d upwellings or fronts associated with coastal jet currents (e.g. Boyd & Smith 1983, Hutchings et al 1986, Smith e t al.…”
Section: Introductionmentioning
confidence: 99%